The effectiveness of differentiated learning in Geography subject, anthroposphere material, for grade X at SMAN 4 Sidoarjo - Widanti, Ni Nyoman Sri; Rindawati, Rindawati; Muzayanah, Muzayanah; Chanthoeurn, Dock (Jurnal Teori dan Praksis Pembelajaran IPS, 2023)
Students play a crucial role in the learning process at school, and creating a fun and engaging learning environment that can positively impact their interest and active participation. However, accommodating the diverse learning styles and needs of students can be a challenge for teachers. To address this, differentiated learning activities are considered appropriate, as they focus on meeting the individual needs of students and allow educators to respond effectively in the classroom. This study aims to assess the effectiveness of differentiated learning in improving the activity and learning outcomes of Grade X Geography students, specifically focusing on the Anthroposphere material at SMAN 4 Sidoarjo during the academic year 2022/2023. To investigate the effectiveness of differentiated learning, a one-shot case study experimental design was employed. The study involved 40 students and utilized the one-shot case study model. The results revealed that the implementation of differentiated learning effectively improved the activity and learning outcomes of Grade X-C Geography students in relation to the Anthroposphere material at SMAN 4 Sidoarjo during the academic year 2022/2023.